Estraneo uguale a straniero. La giustizia riparativa per i minorenni come potenziale strumento di inclusione - De Felice, Deborah; Oliveira, Leandro; Rodrigues, Ellen (SocietàMutamentoPolitica, 2020)
The paper reflects on the potential of some restorative justice tools read as inclusion practices in the juvenile criminal sphere and extendable to the field of immigrant minors. The scenario involving both types of minors is the context of economic, social and family fragility on which the challenge of inclusion is played – most often missed, in the first case, and, perhaps, future, in the second. The context of analysis is that of a path of mediation experienced in the Brazilian reality. Brazil is a territory with high social stratification that recalls central themes of social and intercultural coexistence. It provides an example of how mediation logic and practices can rise to category and interpretative tools to understand complex and contradictory dynamics of integration and at the same time marginalization and exclusion, which in contemporary times characterize, starting from Simmel’s words, relationships with “the other”, “the stranger”, the “foreigner”.